Representation Imperatives in the Public Mind. (24th June 2019) - Doherty, David; Bryan, Amanda Clare; Willis, Reid; Witry, Paul
Abstract : Objective: Some models of representation posit that high quality representation hinges on legislators adhering to their campaign promises. Others rest on the idea that representatives should respond to prevailing sentiment among their constituents. Still others suggest that legislators have a special obligation to their supporters—the voters who put them into office. We assess how important citizens think it is for elected officials to respond to each of these representation imperatives. Methods: We leverage a national survey experiment that asked respondents to evaluate a Senator whose behavior conformed to or was at odds with each of these modes of representation. Findings: Adhering to campaign promises and responding to prevailing public preferences similarly, and independently, affect evaluations of whether a vote cast by a legislator was appropriate. We also find a pronounced partisan divide in the importance people attach to responding to electoral supporters' preferences. Conclusions: In the aggregate, Americans value each of the three modes of representation we investigate. However, Democrats attach essentially no independent importance to responsiveness to core supporters, while Republicans see this type of responsiveness as just as important as adhering to campaign promises or responding to the broader constituency.